Pengaruh Perekonomian dan Jumlah Penduduk Terhadap Permintaan Bahan Bakar Minyak di Indonesia - Yurlis Sartika; Syamsul Amar (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study aims to analyze the factors that influence the demand for fuel oil in Indonesia. The independent variables of this study are: (X1) Economy, (X2) Total Population. The model chosen in this study is the Random Effect Model (REM). This type of research is descriptive and associative research, the data used in this study are secondary data using panel data techniques during the 2015-2018 period. Documentation data collection techniques obtained from the Central Statistics Agency and BPH Migas. Data were analyzed using the Regression Panel.The results of this study indicate that: (1) The economy has a positive and significant effect on demand for fuel oil in Indonesia. This means that as the economy increases, the demand for fuel oil in Indonesia also increases. Indonesia's energy consumption is dominated by fossil energy, especially fuel. Final energy consumption consists of various sectors, namely households, industry, transportation, commercial, and others. Energy is very much needed in carrying out Indonesia's economic activities, both for consumption needs and for the production activities of various economic sectors. (2) The population has a positive and significant effect on the demand for fuel oil in Indonesia. This means that the greater the population, the higher the demand for fuel oil in Indonesia. From year to year the population of Indonesia as one of the developing countries in the world continues to experience growth. This growth has had various impacts on aspects of human life. One aspect that is quite affected by the increase in population is the use of energy to support the necessities of life which includes the industrial sector, households, transportation and so forth. The greater the population, the greater the energy used.